Construction of a protein-protein interaction biosensor to screen for anti-viral compounds - Eckerström, Tim (My University, 2022)
Viral diseases are an ever present issue. The current covid-19 pandemic comes to mind, but also the Spanish flu, which was one of the deadliest pandemics to ever occur, and the ongoing HIV/AIDS epidemic clearly illustrates the dangers of viral diseases. The most effective tool we have to combat viruses are vaccines. The limitations to vaccines are that they are purely preventative and that certain parts of the population may not be able to receive them. In the case of infection, and for those unwilling or unable to get vaccinated, medication fills an important role. The aim of the project was to develop a biosensor able to screen for protein-protein interaction inhibitors to be utilized as drug candidates for the treatment of viral disease.